Draft precis of evidence to be given before the Departmental Committee on Midwives
1928-09 1928 1920s 6 pages PRIVATE & CONFIDENTIAL. September, 1928. STANDING JOINT COMMITTEE OF INDUSTRIAL WOMEN'S ORGANISATIONS. DRAFT PRECIS OF EVIDENCE TO BE GIVEN BEFORE THE DEPARTMENTAL COMMITTEE ON MIDWIVES. 1. The Standing Joint Committee of Industrial Women's Organisations represents working women organised in the Political Labour, Trade Union and Co-operative Movements, including the Labour Party, Trades Union Congress and Co-operative Union. It represents over 1 million women. Some of the organisations, as, e.g. the Women's Sections of the Labour Party, the Women's Co-operative Guild and the two organisations of wives and daughters of Railway Trade Unionists have special advantages in expressing the point of view of married working women who are more particularly concerned in this question of maternity services. The question of maternal welfare has been specially studied by the Standing Joint Committee during the last eight years and three reports have been prepared by the Committee and presented at National Conferences of Labour Women. The last of these, adopted by the Conference in May, 1928, has since been placed before the Labour Party Conference. 2. The Standing Joint Committee have noted the following terms of reference of the Committee:- "To consider the working of the Midwives Acts with particular reference to the training of midwives and the conditions under which they are employed." 3. The Standing Joint Committee recognise that the special purpose of the Committee is thus confined to the position of the midwife. But it is not possible to deal adequately with the training, status, salary and other conditions of the midwife without considering the other two factors in the care of maternity, namely, the doctor and the Public Health Services in the interests of maternity and child welfare. 4. For the convenience of the Committee therefore we set out here our general scheme for securing the best treatment for mother and baby at birth. (Pp. 14-18 of Report). 5. The first point to which we specially desire to draw attention here is paragraph (h). This is in accordance with the principle laid down in the Maternity Convention adopted at the International Labour Conference at Washington in 1919, but not yet ratified by the British Government though supported by its representatives at the Conference. The Labour Movement has consistently urged that its provisions for free medical and nursing care should be adopted and extended from women working for wages to all women. 6. The reason for setting up the Departmental Committee was, we understand, the desire to reduce the present high maternal death rate and also the high infantile death rate during the first four years of life. We are convinced that this would be greatly reduced if mothers could have better ante-natal care as well as better attendance at childbirth. The value even of late ante-natal care by the midwife was proved to us during the Miners' Lock-Out. The Women's Committee for the Relief of Miners' Wives and Children organised a scheme for assisting by a small sum of money spent on food and necessary clothes for mother and baby. The Local Committees of women administering the scheme required some proof of the coming confinement such as a note from the midwife or doctor. This 292/824/1/116